STUDI PARTISIPASI PENGANGGARAN, PENGENDALIAN ANGGARAN, STRUKTUR ORGANISASI TATA KERJA (SOTK), BUDAYA NASIONAL, PRILAKU DISFUNGSIONAL DI PEMERINTAH KOTA DAN KABUPATEN BEKASI - Sabaruddinsah Sabaruddinsah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
This study aims to test whether the national culture can bertindah as a mediating variable in therelationship between budget participation, budget control and working procedures of theorganizational structure of the dysfunctional behavior of the officials in the implementation ofregional autonomy in the City and Bekasi. The method used is descriptive quantitative method with acorrelation approach. Sampling technique in this study using the technique side perposive samplingtechnique using specific criteria. To analyze the data used Structural Equation Modeling (SEM) withSmartPLS program (Partial Least Square). The test results of the parameter coefficients of eachvariable is participation showed positive influence 0222 budget, with the t-statistic values of 3,773and significant at the 0.05, the coefficient of the variable parameters control the budget withdysfunctional behavior positively influences menunujukkan 0786, with a value of t-statistics for 22 116and significant at 0.05, and the coefficient of the variable parameters governance organizationalstructure working with the national culture menunujukkan no positive effect 0.313, with t-statisticvalues of 8,063 and significant at 0.05. From the results of this study concluded that budgetaryparticipation variable positive and significant effect on dysfunctional behavior, budget control provedto significantly influence the national culture and national culture proved positive and significantconsequences for dysfunctional behavior and participation variable budgeting, budgetary control andorganizational structure affects the functioning of the dysfunctional behavior, but national culture isnot a variable that can strengthen or weaken the influence of national culture but it is one that arisesamong the variables that can be directly related to management control systems and dysfunctionalbehavior.